Revisiting Aire and tissue-restricted antigens at single-cell resolution - Matsumoto, Minoru; Yoshida, Hideyuki; Tsuneyama, Koichi; Oya, Takeshi; Matsumoto, Mitsuru (Frontiers in Immunology, 2023)
The thymus is a highly specialized organ that plays an indispensable role in the establishment of self-tolerance, a process characterized by the “education” of developing T-cells. To provide competent T-cells tolerant to self-antigens, medullary thymic epithelial cells (mTECs) orchestrate negative selection by ectopically expressing a wide range of genes, including various tissue-restricted antigens (TRAs). Notably, recent advancements in the high-throughput single-cell analysis have revealed remarkable heterogeneity in mTECs, giving us important clues for dissecting the mechanisms underlying TRA expression. We overview how recent single-cell studies have furthered our understanding of mTECs, with a focus on the role of Aire in inducing mTEC heterogeneity to encompass TRAs.